Biochemical evolution in response to intensive harvesting in algae: Evolution of quality and quantity. (1st May 2018) - Marshall, Dustin J; Lawton, Rebecca J; Monro, Keyne; Paul, Nicholas A
Abstract: Evolutionary responses to indirect selection pressures imposed by intensive harvesting are increasingly common. While artificial selection has shown that biochemical components can show rapid and dramatic evolution, it remains unclear as to whether intensive harvesting can inadvertently induce changes in the biochemistry of harvested populations. For applications such as algal culture, many of the desirable bioproducts could evolve in response to harvesting, reducing cost‐effectiveness, but experimental tests are lacking. We used an experimental evolution approach where we imposed heavy and light harvesting regimes on multiple lines of an alga of commercial interest for twelve cycles of harvesting and then placed all lines in a common garden regime for four cycles. We have previously shown that lines in a heavy harvesting regime evolve a "live fast" phenotype with higher growth rates relative to light harvesting regimes. Here, we show that algal biochemistry also shows evolutionary responses, although they were temporarily masked by differences in density under the different harvesting regimes. Heavy harvesting regimes, relative to light harvesting regimes, had reduced productivity of desirable bioproducts, particularly fatty acids. We suggest that commercial operators wishing to maximize productivity of desirable bioproducts should maintain mother cultures, kept at higher densities (which tend to select for desirable phenotypes), and periodically restart their intensively harvested cultures to minimize the negative consequences of biochemical evolution. Our study shows that the burgeoning algal culture industry should pay careful attention to the role of evolution in intensively harvested crops as these effects are nontrivial if subtle.